The impact of interactions between various systems caused by three consecutive years of La Nina events on the abnormal summer high temperatures in China in 2022 - Boyu, Chai (Frontiers in Marine Science, 2024)
In the summer of 2022, like in many other regions of the world, an unprecedented period of continuous high-temperature weather occurred in eastern China. The degree and duration of this event far exceeded normal standards. Between 2020 and 2022, the tropical Pacific experienced the most significant three-year consecutive La Nina event recorded in recent decades. We investigate linkages between these events: the high-temperature response in eastern China and Asia under the background of such La Nina events. Development of summer La Nina events contributed to a high-temperature heat wave during the summer of 2022. Rapid development of these events in the third year exacerbated negative Indian Ocean Dipole phases because of energy accumulation from abnormal easterly winds. The combined effects of the negative Indian Ocean Dipole phase and La Nina provided background field support that strengthened the West Pacific Subtropical High (WPSH) and the Iranian High, leading to high terrestrial temperature anomalies. An empirical orthogonal function (EOF) analysis of the vertical velocity in the middle and low latitudes of the tropical Indian Ocean and the Asian continent reveals the first two empirical orthogonal function modes to be conducive to the strengthening of Walker circulation in 2022. These two main modes jointly reflect the rising movement of the equatorial East Indian Ocean and South China Sea in 2022, and the sinking movement to the west of the Tibet Plateau and eastern China, which was conducive to generating high temperatures in eastern China. Finally, the South Asian High was affected by the La Nina event that lasted for three years, showing a strong trend towards the north, thus making an important contribution to this high temperature.